Mesto Velikega slovarja tujk v slovenski leksikografiji - Holz, Nanika (Jezik in slovstvo, 2005)
The article focuses on Veliki slovar tujk (Great dictionary of foreign words) published by the Cankarjeva založba publishing house in 2002. The dictionary of foreign words is not typical as far as all lexicografic traditions are concerned, which is due to several reasons: word formation, phonetics, purism, and, undoubtedly, the important role played the number of speakers of a certain language and their understanding of what is "foreign" and what "native". For the purpose of evaluation and the placement of this dictionary within Slovene lexicography, a sample of entries was analysed and compared with the sources, listed in the dictionary as being primary, and also with FIDA, a refenence corpus of the Slovene language. The analysis showed that the dictionary contains many terminological expressions, making this dictionary in fact a large terminological dictionary. In general, it is possible to observe after the analysis that such a concept of dictionary-making is no longer up-to date; a question can also be posed about the purpose of new (revised) editions of old lexicographic reference works, since contemporary users are increasingly demanding and expect lexicographic products of high quality.
Keywords: Slovene; slovenščina; leksikografija; lexicography; tujke; slovarji; Veliki slovar tujk